2013
DOI: 10.1002/tea.21135
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a master's program on teachers' science instruction: Results from classroom observations, teacher reports, and student surveys

Abstract: This study examines the impact of a new master's degree program on the instructional practices of K‐8 in‐service teachers. This 2.5‐year master's program was designed to deepen in‐service teachers' knowledge in science and mathematics and promote greater use of reform‐oriented instruction. Teachers' instructional practices were captured annually through classroom observations, student reports, and teacher self‐reports. Based on the results of the first 2 years of program implementation, there was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To realize the implementation of integrated STEM education, professional development should be designed with the specific needs of teachers in mind, including pedagogy, content knowledge and teacher attitudes and beliefs (Copur-Gencturk, Hug, & Lubienski, 2014;Dass, 2001). Professional development programs which include attention to these contextual constructs have become a central strategy in efforts to achieve the goal of education reform with the goal of improving students' academic performance (Johnson, Sondergeld, & Walton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To realize the implementation of integrated STEM education, professional development should be designed with the specific needs of teachers in mind, including pedagogy, content knowledge and teacher attitudes and beliefs (Copur-Gencturk, Hug, & Lubienski, 2014;Dass, 2001). Professional development programs which include attention to these contextual constructs have become a central strategy in efforts to achieve the goal of education reform with the goal of improving students' academic performance (Johnson, Sondergeld, & Walton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although teachers and designers often work together to design computersupported inquiry curricula, how these tools are enacted by individual teachers may be very different (Puntambekar et al, 2007). Researchers have found that when teachers were more comfortable with teaching a particular topic, they are more likely to encourage students to question, investigate, and discuss around core scientific concepts (Copur-Gencturk, Hug, & Lubienski, 2014;Sinclair, Naizer, & Ledbetter, 2011;Van Duzor, 2011). In addition, longitudinal professional development programs with ongoing support throughout the academic years appear to help teachers enhance the quality of classroom discourse (Copur-Gencturk, Papakonstantinou, & Parr, 2013), use more open-ended questions, and encourage students to consider alternative explanations (Sandholtz & Ringstaff, 2013).…”
Section: Computer-supported Inquiry and Classroom Culturementioning
confidence: 99%